Draft Third Five Year Plan 1961-66 (Volume-VI) Health Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1961)
There was no integrated programme for the development of health services in the First Five Year Plan. However, a few Dispensaries were established in the colonisation areas and other parts of the Territory to meet the health needs of rural population. There were 4 Hospitals and 21 Dispensaries at the end of 1955-56. Measures were also undertaken for improving drinking water supply in a few villages.
Andaman and Nicobar Administration